2016
DOI: 10.1590/1516-3180.20161341t2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and cost-effectiveness of home palliative care services for adults with advanced illness and their caregivers

Abstract: The results provide clear and reliable evidence that home palliative care increases the chance of dying at home and reduces symptom burden in particular for patients with cancer, without impacting on caregiver grief. This justifies providing home palliative care for patients who wish to die at home. More work is needed to study cost-effectiveness especially for people with non-malignant conditions, assessing place of death and appropriate outcomes that are sensitive to change and valid in these populations, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
145
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(153 citation statements)
references
References 3 publications
3
145
1
4
Order By: Relevance
“…Both hospital and home palliative care services have been shown to significantly improve patient outcomes and caregiver satisfaction with care (Gomes et al, 2013;Higginson and Evans, 2010). By being present and by actively engaging in caregiver support, the multidisciplinary team can make a significant difference in caregivers' lives (Northfield and Nebauer, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Both hospital and home palliative care services have been shown to significantly improve patient outcomes and caregiver satisfaction with care (Gomes et al, 2013;Higginson and Evans, 2010). By being present and by actively engaging in caregiver support, the multidisciplinary team can make a significant difference in caregivers' lives (Northfield and Nebauer, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…16 Lately, some systematic reviews reported that PC has been proven to be more effective than standard approaches. [17][18][19] Conversely, little is known about the effectiveness of interventions focused on QoL measurement in PC clinical settings. Starting from the definition of complex interventions proposed by the Medical Research Council (MRC), 20 we lately argued that a procedure of QoL assessment in clinical practice (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, yes, as long as it is developed with cultural sensitivity. [1][2][3][4] It is a community movement.…”
Section: Discussionmentioning
confidence: 99%
“…Its compassionate multidisciplinary team approach has proved effective physically, emotionally, and financially to alleviate pain and suffering and to further offer holistic comfort care to the recipients and their families. [1][2][3][4] Its growth has been gradual but steady, from only 1 facility in 1974 to 5800 facilities in 2013 in the United States. 5 Hospice care facilities served on 44.6% of all deaths in the United States.…”
Section: Introductionmentioning
confidence: 99%